A DESCRIPTIVE STUDY ON POLITENESS STRATEGIES IN “ALADDIN” MOVIE - Didit Wahyu Permadi; Tri Mulyati; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
This research is a descriptive study on the use of politeness strategy in movie. The researcher used a descriptive qualitative approach. This research focused on describing politeness strategies used by the main characters of Aladdin movie. The data were analyzed from conversation script in form of utterance. The researchers used analysis method by Miles and Huberman, namely data reduction, data display, and conclusion drawing/verification. The research results showed that the types of politeness strategies used by the four main characters in the film Aladdin are the bald-on record strategy, positive politeness strategies, negative politeness strategies, and off-record strategies. Bald on record is the most widely used. It appeared 11 times (37%). It is followed by positive politeness which are uttered 7 times (23%) and off record which are also uttered 7 times (23%). The forth is negative politeness that uttered 5 times (17%). The researcher suggest to the English teachers to use Aladdin movie as teaching resource for politeness strategy. The researcher also suggested to the students could apply the politeness strategy in their life especially with the teachers and mates during learning process. For the further researcher, there are many aspects which can be analyzed about Pragmatics including politeness strategy. The reseracher suggests to the other researchers to analyze other aspects of Pragmatics in different works.